Berberine Prolongs Mouse Heart Allograft Survival by Activating T Cell Apoptosis via the Mitochondrial Pathway - Ma, Yunhan; Yan, Guoliang; Guo, Junjun; Li, Fujun; Zheng, Haiping; Wang, Chenxi; Chen, Yingyu; Ye, Yuhan; Dai, Helong; Qi, Zhongquan; Zhuang, Guohong (Frontiers in Immunology, 2021)
Berberine, which is a traditional Chinese medicine can inhibit tumorigenesis by inducing tumor cell apoptosis. However, the immunoregulatory of effects berberine on T cells remains poorly understood. Here, we first examined whether berberine can prolong allograft survival by regulating the recruitment and function of T cells. Using a major histocompatibility complex complete mismatch mouse heterotopic cardiac transplantation model, we found that the administration of moderate doses (5 mg/kg) of berberine significantly prolonged heart allograft survival to 19 days and elicited no obvious berberine-related toxicity. Compared to that with normal saline treatment, berberine treatment decreased alloreactive T cells in recipient splenocytes and lymph node cells. It also inhibited the activation, proliferation, and function of alloreactive T cells. Most importantly, berberine treatment protected myocardial cells by decreasing CD4+ and CD8+ T cell infiltration and by inhibiting T cell function in allografts. In vivo and in vitro assays revealed that berberine treatment eliminated alloreactive T lymphocytes via the mitochondrial apoptosis pathway, which was validated by transcriptome sequencing. Taken together, we demonstrated that berberine prolongs allograft survival by inducing apoptosis of alloreactive T cells. Thus, our study provides more evidence supporting the potential use of berberine in translational medicine.